Difficulties in histological diagnosis of a case of lymphoma secondary to acute renal failure in a nephrology department in sub-Saharan Africa - Guei Monlet Cyr; Yao Kouamé Hubert; N'DahKouamé Justin; Lagou Delphine Amelie; Tia Weu Melanie; Konan Serge Didier; Choho Carole; Diopoh Sery Patrick; Ackoundou-N'Guessan Kan Clément; Gnionsahé Dazé Appolinaire (Society of Diabetic Nephropathy Prevention, 2020)
Nephrology is a new discipline in sub-Saharan Africa. For a better management of various nephropathies, histological data are necessary in terms of diagnosis, therapy as well as prognosis. However, performing renal needle biopsy is very challenging. We are reporting inadequacy of human, material and financial resources for histological data collection through a case of 21-yearold patient with lymphoma complicated by acute renal failure (ARF).